Charcot arthropathy of the foot and ankle: an update - Montechi, João; Barros, Weslen; Godoy-Santos, Alexandre; Sposeto, Rafael; Macedo, Rodrigo; Fernandes, Tulio (Journal of the Foot & Ankle, 2021)
To critically evaluate the current literature on the etiopathogenesis of Charcot neuroarthropathy, its diagnostic methods and therapeutic management. Methods: We searched for studies that related Charcot arthropathy with a location in the foot and ankle in the PUBMED and MEDLINE databases. Results: A total of 52 studies were used for this analysis. Conclusion: Charcot neuroarthropathy is a serious disease with significant potential to impact patient quality of life. Although its pathogenesis still raises much controversy, neuropathy seems to have a central role, leading to a trauma, injury, and inflammation cycle. Level of Evidence V; Therapeutic Studies; Expert Opinion.